An assessment and analysis of duty- bearers realising the right to food among children under the age of 18 years in Masiphumelele, Cape Town - Vincent, Susan Melanie (Stellenbosch : Stellenbosch University, 2015)
Thesis (MNutr)--Stellenbosch University, 2015.